Potensi Retribusi Parkir dan Pajak Restoran di Kawasan Wisata Kuliner Baiman Banjarmasin - Khansa, Ridha Muthia; Nuryadin, M. Rusmin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The purpose of this research is (1) to find out how much potential restaurant taxes are in theculinary tourism area of Baiman Banjarmasin and (2) to find out how much potential parkingfees are in the culinary tourism area of Baiman Banjarmasin. The study uses primary datafrom interviews with restaurant owners and parking lot managers in the Baiman Banjarmasinculinary tourism area. The quantitative descriptive method is used in this study. The results ofthis study indicate that the restaurant tax in the culinary area of Baiman Banjarmasin hasconsiderable potential for regional income. The calculation of parking fees in the culinary areaof Baiman Banjarmasin also has enormous potential if managed optimally by the Banjarmasincity government, especially the Banjarmasin city parking UPTD.Keywords: Restaurant tax, Parking Retribution.